IMPROVING THE SOIL BARRIER FUNCTIONS UNDER THE THREAT OF CADMIUM CONTAMINATION IN ORDER TO OBTAIN ECOLOGICALLY SAFE YIELDS OF WHITE CABBAGE - Snitynskyi В.; Dydiv А.; Kachmar Н.; Ivankiv М.; Datsko Т. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
Soil is a specific component of the biogeosphere. It is able to accumulate pollutants and is the natural buffer for them. Soil is an intermediate or final link in the translocation of chemical elements and various compounds in the cycle: atmosphere – hydrosphere – living matter – lithosphere. Approximately 90 % of heavy metals (HM) entering the environment are accumulated in soils, polluting the adjacent environments and biota, or undergo sedimentation (fixation in the solid phase). The influx of such heavy metals as Cd, Pb, Zn, Ni, Hg into agroecosystems significantly exceeds the natural removal of them and inclusion in the biogeochemical cycle. All main cycles of the natural migration of heavy metals in the biogeosphere (aqueous, atmospheric, biotic) begin with the lithosphere. Anthropogenic pollution of soils complements these cycles, and if soils do not «cope» with their sedimentation, or poorly «work» as buffers, additional agrotechnical measures are needed to prevent contamination of agricultural products with heavy metals. It is in the soil that their mobilization and formation of various migratory forms and toxic backgrounds takes place. The vast majority of heavy metals that have reached the soil surface are retained by organic components (fixed in the upper humus horizons) or fixed by its mineral component and undergo sedimentation. To improve the barrier functions of the soil which is contaminated with heavy metals in order to obtain ecologically safe agricultural products, organic and bacterial fertilizers are applied, siderates are used, proper rotation of crops is carried out in crop rotation, complex mineral fertilizers and calcium ameliorants are rationally used, that help maintain favorable physical and chemical properties of the soil and increase its fertility. These and other measures increase the buffering capacity and sedimentation potential of soils in relation to mobile forms of heavy metals and other xenobiotics. The research has established, that the use of an organic and organic-mineral fertilizer system in combination with liming of the soil at the norm of Biohumus 8 t/ha + CaСО3 5 t/ha and N64P64K64+ Biohumus 4 t/ha + СaСО3 5 t/ha contributes to activation of the soil barrier functions, which has been manifested in a decrease in the mobility of Cd2+ ions in the soil and a decrease in their translocation into white cabbage plants at all levels of the simulated soil contamination with cadmium. It was found that the lowest concentration of mobile forms of cadmium in the soil of 0.051 and 0.063 mg/kg, the lowest transition of the element from the gross form to the mobile form of 3.30 and 4.67 % with a hazard ratio of 0.07 and 0.09 was noted on the control background in specified variants of the experiment. Accordingly, on these variants, the hazard coefficients of element concentration in heads of cabbage were also the lowest (0.13 and 0.21), which indicated the ecological safety products of white cabbage and the feasibility of using methods of chemical reclamation of the soil contaminated with heavy metals. A strong correlation (r = 0.96) was found between the concentration of mobile forms of Cd2+ in the soil and the concentration of the element in white cabbage plants.